Revised capacity assessment of Ravishankar Sagar reservoir using remote sensing and GIS, Chhattisgarh, India - DHRUW, GUNJA; AGRAWAL, NARENDRA; DHANKAR, BHUPENDRA (Journal of Soil and Water Conservation, 2026)
Reservoir storage capacity is gradually reduced by sedimentation, and accurately assessing the sedimentation rate is crucial for estimating the reservoir’s lifespan and ensuring the optimal performance of reservoir operation. Conventional methods are utilized to determine reservoir capacity and sedimentation in a reservoir. However, Remote Sensing and GIS techniques provide an alternative approach to determining the current capacity of a reservoir. These methods offer advantages due to their straightforward analysis procedures and the repetitive coverage they provide through imagery. Additionally, surveys that utilize remote sensing data are faster, more cost-effective, and more reliable. This technique computes the loss of storage capacity and sedimentation in Ravishankar Sagar Reservoir (RSR), situated in Dhamtari district, Chhattisgarh state, India. Utilizing the Sentinel-2 digital data from the IRS-1D/P6 Indian Remote Sensing (IRS) satellite, multiple scenes have been imported to distinguish pixels with water and without water. ArcGIS has been utilized for image processing functions like image slicing, rationing, and Normalized Difference Water Index (NDWI) computation. The updated reservoir’s capacity was calculated using the Prismoidal formula, which takes into account the revised water spread area at different elevation levels. The final result indicates that the reservoir has accumulated 83.196 MCM of sediment at the end of 2020; after 41 years, the percentage of capacity lost is 9.14%, with a sedimentation rate of approximately 1.980 MCM/year.